Technological advances in elite marathon performance - Senefeld, J. W.; Haischer, M. H.; Jones, A. M.; Wiggins, C. C.; Beilfuss, R.; Joyner, M. J.; Hunter, S. K. (Journal of Applied Physiology, 2021)
There is scientific and legal controversy about recent technological advances in performance running shoes that reduce the energetic cost of running and may provide a distinct competitive advantage. To better understand the potential performance-enhancing effects of technological advancements in marathon racing shoes, we examined the finishing times and racing shoes of the top 50 male and 50 female runners from the World Marathon Major series in the 2010s before and after the introduction of new Nike shoe models (4%, NEXT%, Alphafly, and other prototypes; herein referred to as "neoteric Nikes"). Data for racing shoes were available for 3,886 of the 3,900 performances recorded at the four annual marathons in Boston, London, Chicago, and New York. In full cohort analyses, marathon finishing times were 2.0% or 2.8 min (138.5 ± 8.1 min vs. 141.3 ± 7.4 min, P < 0.001) faster for male runners wearing neoteric Nikes compared with other shoes. For females, marathon finishing times were 2.6% or 4.3 min (159.1 ± 10.0 min vs. 163.4 ± 10.7 min, P < 0.001) faster for runners wearing neoteric Nikes. In a subset of within-runner changes in marathon performances (males, n = 138; females, n = 101), marathon finishing times improved by 0.8% or 1.2 min for males wearing neoteric Nikes relative to the most recent marathon in which other shoes were worn, and this performance-enhancing effect was greater among females who demonstrated 1.6% or 3.7 min improvement (P = 0.002). Our results demonstrate that marathon performances are substantially faster when world-class athletes, and particularly females, wear marathon racing shoes with technological advancements.